The Analysis Study of Nutritional Management of Patient with Obesity: A Clinical Nutrition Systematic Review - Caroline, Caroline; Cynthia, Cynthia (International Medical Journal Corp. Ltd, 2024)
Background: Obesity is a multifactorial condition influenced by a combination of genetic, behavioral, socioeconomic, and environmental factors. The first-line approach for managing obesity typically involves dietary interventions. This systematic review aim to evaluate the current evidence on various nutritional management for obesity based on the literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Different nutritional strategies offer distinct benefits for managing obesity, with Mediterranean, anti-inflammatory, and low-carbohydrate diets showing promise. The key lies in promoting adherence and maintaining weight loss through tailored, sustainable interventions.